The Students’ Perception to Artificial Intelligence (AI) in English Language Learning - Karmila, Evi; Fakhruddin, Zulfah; Dalle, Ambo; Saepudin, Saepudin; Mujahidah, Mujahidah (IAIN KENDARI, 2026)
In the era of digital transformation, the integration of using artificial intelligence has gained significant attention, especially in English language learning study in the English Education Program at State Islamic Institute (IAIN) Parepare. This study identifies students’ perceptions on the use of Artificial Intelligence in English Language Learning and also the advantages and challenges students in State Islamic Institute (IAIN) of Parepare. Using the Technology Acceptance Model (TAM) as the theoretical foundation, the study focuses on two key constructs: Perceived of Usefulness (PU) and Perceived Ease of Use (PEoU). Employing a descriptive quantitative approach, data were collected from 30 participants, comprising 15 students from the 3rd semester and 15 students from the fifth semester, through structured questionnaires using a semantic differential scale. Findings reveal that students are highly useful and relatively easy to use in English language Learning. The students reported higher mean scores in both PU (4,130 = very useful) with positive perception and PEoU (4,213= very easy), reflecting their professional experience and familiarity with technology integration. Students, while positive, exhibited slight scores in both Advantages (4,283= Highly Advantages) and Challenges (4,213= Very High Challenges), highlighting variability due to differences in digital literacy and access. The study underscores the need for improvement and support in technical independence and initial learning phases.